Hope and Utopianism in everyday life in an aspirational city of coal - Luckett, Thembi (Nothemba) Kate (My University, 2021)
The material and social worlds are unfinished, with multiple ontological potentialities existing in the present. This thesis explores the gap of the ‘not yet’ in shaping everyday life through hopeful cognitive and affective attachments to different futures. I argue that hope matters, and as a force in the world, hopes are both generated within and generative of specific space-times. As such, hopes and manifest and function differently across space-times. I thus specifically explore hopes in the everyday in the town of Lephalale and its surrounds in the Limpopo province of South Africa. The analysis of hope in ordinary people’s everyday lives has been largely absent in the field of utopian studies. This research project aims to address this lacuna through an interdisciplinary and grounded, empirical study with a specific focus on the concept of hope in the everyday. Lephalale developed around a coal mine and coal-fired power station in the 1980s. Recently, with the development of Medupi Power Station and possible future coal developments, it has become a place of interest and attraction. Given that it holds South Africa’s largest remaining coal reserves, this locality is of particular significance as a contradictory site of aspiration and destruction. The South African economy relies almost entirely on fossil-based energy. This trajectory continues in the face of a global existential catastrophe: anthropogenic, or human-induced, climate change. For these reasons, this site allows an analysis of hope and possibilities in a contradictory space-time of modernist imaginaries of the future and fossil fuel catastrophe that forecloses habitable futures. In order to explore hope in the everyday in Lephalale, this thesis brings the work of Ernst Bloch, the philosopher of hope, into conversation with that of Henri Lefebvre, the theorist of social space. Fully cognisant of the ontological messiness of everyday life, but to sharpen the analysis, I introduce two new analytic categories: ‘reproductive hope’ and ‘transformative hope’. I use reproductive hope to analyse practices and discourses of production and consumption, which are aspirational of a ‘good life’. Such hopes reproduce the given order, locking people into repetitive cycles of social being that permanently defer the ‘good life’. I argue that, while mainly reproductive of the dominant space-time, such hopes can lead to motion, which is meaningful and can open up surpluses from which to transform subjectivities and conditions of life. By way of contrast, I argue that transformative hope shifts the terrain of possibility. Affective and cognitive connections to the present are disrupted or reconfigured so that alternative futures are provoked. As such, these hopes relate more to becoming, generating possibilities for transforming the everyday. Finally, this thesis engages with hope as method. Hope as method is an orientation to knowledge and philosophy that is not only backwards-looking or contemplative of the past. An orientation towards the future pushes knowledge at its limits, exploring and thinking through possibilities and potentialities. This calls for a capacity to understand and read the world as unfolding from a standpoint of openness. Hope as method is necessarily an inter-subjective method that aims to generate contestations and possibilities as part of the broader project of imagining and creating alternative futures.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021